Edukasi Pengenalan Mie Sehat Organik Dari Buah Dan Sayuran - Rozanatul Muti’ah; Nur Aisyah; Sylvia Oktaviani; Kuspitasari Kuspitasari; Nur Aprillah Kartini; Agustiawan Agustiawan (Asosiasi Dosen Akuntansi Indonesia, 2020)
Community Service on Education on the Introduction of Healthy Organic Noodles from Fruits and Vegetables in order to provide knowledge to the public about the dangers of consuming instant noodles and starting to switch to consuming organic healthy noodles. The goal is to increase public awareness in Marpoyan Damai District, Perhentian Marpoyan Village, RW 11 RT 03, Jl. Inpres Gg. Harmoniousness in the importance of maintaining health by consuming healthy food by creating innovations in food processing that can be consumed by all groups, and giving awareness to housewives that creativity can help increase income. The method used in this Community Service activity is a learning system that is carried out by online training and is equipped with modules and video tutorials on how to make organic healthy noodles. The techniques used in providing the training are lectures, discussions and question and answer methods. The results that have been achieved so far, namely the 2-month service program have made the community have basic knowledge about healthy organic noodles from fruit and vegetables and the manufacturing process.